2022
DOI: 10.3389/fmars.2022.991253
|View full text |Cite
|
Sign up to set email alerts
|

Fisherwomen’s Indigenous and local knowledge - the hidden gems for the management of marine and freshwater resources in Fiji

Abstract: Fisherwomen in Fiji play a vital role in the daily sustenance of their families and they use their Indigenous and local knowledge to harvest resources. Marine and freshwater resources harvested by fisherwomen contribute to the primary protein intake of their families, particularly for those who have limited or no access to other animal products or plant proteins. Over a span of three decades, Fiji experienced an influx in the documentation of women’s contribution and need for fisherwomen's recognition in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…to prevent fish mortality in transportation [ 44 , 59 ]. In Fiji, however, Citrus reticulata is used as a seasonal cue for fish presence and Erythrina variegate is used to signify octopus season [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…to prevent fish mortality in transportation [ 44 , 59 ]. In Fiji, however, Citrus reticulata is used as a seasonal cue for fish presence and Erythrina variegate is used to signify octopus season [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the bivalves found at research locations that depend on mangroves is Anadara granosa (Linnaeus, 1758); this species consumes plankton and other microorganisms that live in mangrove areas. Apart from that, the presence of mangroves is also vital in maintaining sediment during tides as a habitat for the bivalves' life cycles (Cantrell 2022;Kitolelei et al 2022). Gastropod and bivalve species associated with mangrove vegetation at the research locations are shown in Figures 2 and 3.…”
Section: Diversity Of Gastropods and Bivalvesmentioning
confidence: 99%